ISOLASI BAKTERI SELULOLITIK PENDEGRADASI SELULOSA DARI KOMPOS - Arifin, Zainul; Gunam, Ida Bagus Wayan; Antara, Nyoman Semadi; Setiyo, Yohanes (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 1 (2019): Maret, 2019)
This study aimed to isolate cellulolytic bacteria that have the potential to degrade cellulose taken compost samples from Temesi and Bondowoso, this study was also conducted to determine the ability of bacteria to degrade cellulose based on Congo red test and filter paper degradation test. All isolates were tested for cellulolytic activity using soluble Carboxymethyl Cellulose (CMC). Characterization was carried out by growing selected pure isolates on CMC media and then dripping 0.1% congo red to test the cellulolytic potential (cellulolytic potential was characterized by the emergence of clear zones around the colony). The results of isolation of bacteria obtained 38 isolates, namely 26 Bondowoso sample isolates and 12 Temesi isolates that were able to grow and utilize cellulose as a carbon source. But only fourteen isolates produced clear zones in the Congo red test with diameters ranging from 1.66  cm to 6.76 cm. Six isolates that have the largest diameter s clear zone, were tested for  degradation of filter paper  (Whatman no. 1). Isolates bacteria of B2 S8 obtained from Bondowoso compost samples has the highest ability to degrade cellulose on Whatman paper no. 1 as much as 51.30%. Keywords : Compost, Isolation, Screening, Cellulolytic Bacteria.